Intestinal motility andnervous system effects dose-response curvefor the interaction between Jotropha curcas L. and metoclopramide - Zavala-Flores , Ernesto (2013)
Objectives: Determinate the dose–response relationship with respect to intestinal motility and the nervous system, of the interaction between the ethanol extract of the J. curcas L. seed and metoclopramide Methods: 90 albino mice were used, which were divided into 10 interaction groups that received 0.5 mg Kg oral (PO) metoclopramide as a fixed dose, and they also received progressively increased doses (100 to 1000 mg/Kg) of an ethanol extract of J. curcas L. seeds. Five additional groups received 0.5 mg metoclopramide PO, 1.5 mg/Kg atropine, 800 mg/Kg J. curcas L., and 0.1 ml/10g distilled water. All groups received oral 5% activated charcoal, 0.1 ml/10g as an intestinal marker. We used the technique described by Arbos et al. for assessing intestinal motility and Irwin's test for assessing the nervous system. The statistical validation of intestine dynamics was performed using Shapiro-Wilk, 1-tailed ANOVA, Tukey, Newman-Keuls, Kruskal-Wallis and Pearson correlation tests. We used the Chi-square method with Yates correction and Fisher's exact method when performing Irwin's test. Results: The percentages of charcoal runs in the 2nd, 7th, 8th, 9th, and 10th interaction groups were 56.8%, 34.54%, 31.85 and 24.57%, compared to 56.3% (metoclopramide) and 27.66% (control). The Irwin test showed these neurological effects: piloerection, sedation, increased respiratory rate and lethality. Conclusions: We proved there is antagonism between the ethanol extract of J. curcas L. seeds and metoclopramide. We also found the concomitant occurrence of neurotoxic effects.